EFFECT OF DEFFERENT LEVELS OF TURMERIC SUPPLEMENTATION WITH DIET ON HUMORAL IMMUNE RESPONSE TO NEWCASTLE AND INFECTIOUS BURSAL DISEASE VIRUS AND HISTOPATHOLOGICAL CHANGES OF SOME INTERNAL ORGAN OF BROILER CHICKENS - M. Shihab, I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
In this study, evaluated the effect of turmeric dietary addition on immune response against the Newcastle disease virus (NDV) and Infectious bursal disease (IBDV). and histopathological changes in some internal organs was evaluated in 42 day old broiler chicks. ninety-six Ross broiler chicks were reared from 1 to 42 days old and divided randomly into four groups, Feed and drinking water were offered ad libitum. Group1 (G1) received turmeric (0.2%), while group2 (G2) received turmeric (0.4%), Group3 (G3) received turmeric (0.6 %) and group4 (G4) was the control positive received basal diet . At the end of the trial five birds from each treatment were slaughtered for assessment of histological section, take same of organ (liver , spleen , and bursa of Fabricius) at 42 day. Results of ELISA test titer revealed differences among various treatment groups at the end of the experiment. mean ELISA test values of G2 revealed a higher significant at (P< 0.05) in antibody titers in comparsion with other groups and control. specimen from liver ,spleen and bursa of fabricius were dissected out for histopathological examination and results of microscopic section showed increase in immune response of G2 chicken : of microscopic sections of G2 histopathological changes in the liver tissue revaled mamefisted by focal mononuclear cells aggregation and proliferation of kupffers cells and slight congestion of blood sinusoids and congestion of portal bloob vessels with few infiltration of inflammatory cells .The intrahepatic bile ductless exhibited dilation and hyperplasia of their epithelial linings with slight per portal fibrosis compared with G1,G3 which showed no clear histopathological changes. The microscopic examination of the spleen revaled range from mild (G1 and G3) to moderate hyperplasia of lymphoid follicles in (G2) . histopathological changes in the bursa of fabricius were characterized by moderate follicular hypertrophy especially in G2 as compared with other treated group’s and control .